Sacituzumab for the treatment of triple-negative breast cancer: the poster child of future therapy?. (1st February 2019) - Zangardi, Mark L.; Spring, Laura M.; Nagayama, Aiko; Bardia, Aditya
ABSTRACT: Introduction : Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer that disproportionately impacts younger women and is associated with a poor prognosis. Systemic treatment options for metastatic TNBC (mTNBC) are limited to cytotoxic chemotherapy agents with low response rates. This encouraged the clinical development of sacituzumab govitecan (IMMU-132), an antibody-drug conjugate targeting Trop-2, a potential target in epithelial cancer such as TNBC. Areas covered : We summarize the key features, pharmacokinetics, and the safety and efficacy data of sacituzumab govitecan. We also discuss the future directions of this novel therapeutic agent for mTNBC. Expert opinion : Based on the efficacy and tolerability observed in the phase 1/2 clinical trial, sacituzumab govitecan was granted breakthrough therapy designation by the Food and Drug Administration as ≥3 rd line therapy for mTNBC. Novel treatment modalities for the management of mTNBC are necessary to improve the care of this aggressive disease. Sacituzumab govitecan represents an important advance in the treatment of mTNBC because of its efficacy and tolerability.